Geographic Variation of Particle Size Distribution in the Kuroshio Region: Possible Causes in the Upper Water Column - Yamada, Yosuke; Fukuda, Hideki; Umezawa, Yu; Nagata, Toshi (Frontiers in Marine Science, 2021)
Particle size distribution (PSD) in the ocean is a fundamental property that influences carbon export and food webs; however, PSD variation and its causes in oligotrophic oceans are not entirely clear. Here, we used Laser In-Situ Scattering and Transmissometry to investigate PSD (size range, 5.2 – 119 µm) and related variables at 11 stations in the surface layer (0 – 20 m) of the Kuroshio region of the western North Pacific, where strong current causes dynamic hydrographic and ecological conditions. PSD slopes (range, –3.2 to –4.2), derived from the power law model, were steeper at onshore stations and flatter at oligotrophic stations located offshore and at lower latitudes. Notably, slopes tended to become steeper with increasing chlorophyll a concentration, opposing the generally observed relationship between the two variables, whereas they became flatter with increasing transparent exopolymer particle (TEP) concentration. Possible explanations of the above results are localized occurrence of nanophytoplankton and TEP facilitation of particle aggregation. The results support the hypothesis that PSD slopes are controlled by a multitude of factors, including phytoplankton community dynamics and aggregation processes. To determine whether TEP-induced particle aggregation enhances or suppresses carbon export, we need a better understanding of the nature (porosity, density and sinking velocity) of aggregates in oligotrophic oceans.